Pemanfaatan Air Kelapa Sebagai Cuka Makan Untuk Meningkatkan Nilai Ekonomi Kelompok Tani Udang Sepakat Di Desa Sungai Rengas - Asti, Asti; Youlla, Donna; Khasanah, Dini Afriani (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2026)
Sungai Kakap District is one of the largest coconut-producing areas in Kubu Raya Regency, where coconut cultivation is owned and managed directly by local communities as a primary source of income. The Udang Sepakat Farmer Group in Sungai Rengas Village consists of farmers engaged in coconut production. Farmers generally prefer to sell coconuts in the form of cleaned coconut meat to obtain a higher selling price, while discarding the coconut water as waste. This practice not only leads to potential environmental pollution but also reflects farmers’ limited knowledge regarding the utilization of coconut water. To address this issue, a community service program was implemented by introducing the processing of coconut water into edible vinegar. The program aimed to reduce environmental pollution caused by coconut water waste, provide farmers with knowledge about its potential benefits, and improve their skills in producing value-added products. The implementation method involved educational outreach and practical demonstrations of coconut water vinegar processing. The results indicated an increase in farmers’ understanding of the environmental impacts of coconut water waste, their awareness of coconut water as a resource, and their technical skills in producing coconut vinegar. Farmers’ acceptance of coconut vinegar was positive, as reflected in favorable perceptions of its taste, aroma, color, and processing method, suggesting its potential as an alternative product with economic value. Keywords: Utilization, Waste, Coconut water, Vinegar, Economic value. Kecamatan Sungai Kakap merupakan salah satu wilayah kecamatan sebagai penghasil kelapa terbesar di Kabupaten Kuburaya. Budidaya kelapa dimiliki dan dikelola secara langsung oleh masyarakat setempat sebagai sumber pendapatan. Kelompok Tani Udang Sepakat Desa Sungai Rengas merupakan kelompok tani dengan petani-petani yang menghasilkan kelapa. Petani memilih menjual kelapa dalam bentuk daging buah yang sudah dibersihkan dari tempurungnya untuk mendapatkan harga jual yang lebih tinggi dan membuang air kelapanya sebagai limbah yang berpotensi mencemari lingkungan. Hal ini dikarenakan kurangnya pengetahuan petani terhadap pemanfaatan air kelapa. Melalui kegiatan pengabdian kepada masyarakat ini diberikan solusi tentang pemanfaatan air kelapa sebagai cuka makan. Tujuan kegiatan ini sebagai upaya untuk mengurangi pencemaran lingkungan dari limbah air kelapa dengan memberikan pengetahuan pada petani mengenai manfaat air kelapa dan meningkatkan ketrampilan petani dalam memanfaatkan limbah air kelapa menjadi cuka makan. Metode pelaksanaan dilakukan dengan penyuluhan dan demonstrasi pemanfaatan air kelapa menjadi cuka makan. Hasil kegiatan menunjukkan adanya peningkatan pengetahuan petani terhadap dampak limbah air kelapa, manfaat air kelapa sebagai cuka makan dan keterampilan petani dalam memanfaatkan air kelapa menjadi cuka makan sehingga berpeluang menjadi produk bernilai tambah. Penerimaan petani terhadap produk cuka makan adalah baik berdasarkan persepsi petani terhadap rasa, aroma, warna dan proses pengolahan cuka makan adalah baik. Kata Kunci: Pemanfaatan, Limbah, Air kelapa, Cuka makan, Nilai ekonomi.